(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Occupational health and safety (OHS) has traditionally emphasized the use of personal protective equipment (PPE) as a frontline defense against workplace hazards. However, modern safety philosophy and regulatory frameworks increasingly advocate for higher-order control strategies, such as engineering design modifications and the implementation of robust company policies. This article explores the rationale for prioritizing engineering solutions and organizational controls over PPE in hazard prevention. Drawing from empirical studies, safety engineering principles, and international safety standards, the paper argues that reliance on PPE is often reactive and insufficient, especially in high-risk environments. The article presents a conceptual framework highlighting the hierarchy of controls and demonstrates how proactive safety design and policy enforcement can significantly reduce occupational risks. Recommendations are made for safety managers, engineers, and policymakers to reorient prevention strategies toward sustainable, systems-based approaches that minimize human error and improve overall safety culture. The article concludes that while PPE remains a vital component of occupational safety, it should serve as a last line of defense rather than the primary safeguard.